BRAC review mission, 1994: internal management review and local and national level coordination - BRAC (© BRAC, 2016)
The 1994 BRAC review mission takes place in the context of the continued rapid expansion of BRAC programmes and staffing. BRAC's expansion has been enumerated in terms of AOs and VOs. Group Members and credit disbursed. It has not been visualized geographically, except for the recent district-level map or BRAC activities. Mapping expansion is a tool by which BRAC can examine its spatial expansion in relation to gaps an coverage, and in relation to interactions with GOB and other NGOs.